2012
DOI: 10.1111/j.1467-9221.2012.00871.x
|View full text |Cite
|
Sign up to set email alerts
|

Ideology, Prejudice, and Attitudes Toward Sexual Minority Social Policies and Organizations

Abstract: This study tested the effects of multiple ideologies on support for restrictive policies against gay and lesbian individuals and organizations and if these effects were mediated by sexual prejudice. Social dominance orientation (SDO), conservatism, and right‐wing authoritarianism (RWA) each had significant direct and indirect effects. SDO had the most consistent direct effects in addition to its effects through sexual prejudice. The direct effects of conservatism were smaller and similar in size to its indirec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 38 publications
6
44
0
3
Order By: Relevance
“…For example, studies have revealed two dimensions underlying policy attitudes in diverse European samples-one representing cultural policies and most strongly associated with RWA, and the other representing economic policies and relating most strongly to SDO (Duriez, Van Hiel, & Kossowska, 2005;Van Hiel & Kossowska, 2007). RWA and SDO have also been shown to differentially predict support for dimensions of human rights endorsement (McFarland & Matthews, 2005), harsher criminal sentencing (McKee & Feather, 2008), and restrictive policies against gay and lesbian individuals and groups (Poteat & Mereish, 2012).…”
Section: Differentiating Social and Economic Policiesmentioning
confidence: 98%
“…For example, studies have revealed two dimensions underlying policy attitudes in diverse European samples-one representing cultural policies and most strongly associated with RWA, and the other representing economic policies and relating most strongly to SDO (Duriez, Van Hiel, & Kossowska, 2005;Van Hiel & Kossowska, 2007). RWA and SDO have also been shown to differentially predict support for dimensions of human rights endorsement (McFarland & Matthews, 2005), harsher criminal sentencing (McKee & Feather, 2008), and restrictive policies against gay and lesbian individuals and groups (Poteat & Mereish, 2012).…”
Section: Differentiating Social and Economic Policiesmentioning
confidence: 98%
“…Education level, political conservatism, and LGB interpersonal contact met the a priori decision rule and were included as covariates for the ANCOVA analysis. Because religious fundamentalism significantly relates to both conservative political and religious beliefs (Altemeyer, 2003;Altemeyer & Hunsberger, 1992;Hunsberger, 1996;Hunsberger & Jackson, 2005;Poteat & Mereish, 2012), the veracity of participants' self-assessment of their political and religious conservatism was examined through a comparison with RFS scores. Correlation coefficients between scores on the RFS scale and participants' selfreported religious (r = -.541) and political conservatism (r = -.531) were the strongest.…”
Section: Descriptive Statistics Correlations and Means Testing Datamentioning
confidence: 99%
“…Within the field of religious studies, a considerable amount of attention has been paid to the relationship between conservative religious beliefs and prejudicial attitudes, behaviors, and responses toward LGB individual and social issues. It is beyond the scope and focus of this article to address this area of study; instead, we refer readers to several key and comprehensive resources (Bayer, ; Bowers et al, ; Hunsberger & Jackson, ; IOM, ; Poteat & Mereish, ; Whitley, ).…”
Section: History: From Illness To Affirmationmentioning
confidence: 99%
“…LGB-Affirmative Counselor Education and Religious Beliefs is beyond the scope and focus of this article to address this area of study; instead, we refer readers to several key and comprehensive resources (Bayer, 1987;Bowers et al, 2010;Hunsberger & Jackson, 2005;IOM, 2011;Poteat & Mereish, 2012;Whitley, 2009). Hooker's (1957) landmark research, demonstrating that homosexuality does not represent a clinical entity or pathology, was instrumental in the (a) removal of homosexuality from the DSM and (b) the 1973 acknowledgement by the APA that homosexuality is not a mental disorder.…”
Section: History: From Illness To Affirmationmentioning
confidence: 99%